2017
DOI: 10.1055/s-0043-115737
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Responses to Different Resistance Exercise Protocols in Elderly

Abstract: Increase in muscle mass and strength through resistance exercise (RE) has been highly recommended for healthy aging. On the other hand, RE could lead to acute cardiovascular risks prompted mainly by intense blood pressure elevations and cardiac autonomic imbalance. We compared the cardiovascular responses to three different RE protocols performed by 21 healthy elderly on a leg press machine. The protocols tested were high load (80% 1RM) until muscular failure (HL); low load (30% 1RM) until muscular failure (LL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 51 publications
(57 reference statements)
2
40
0
1
Order By: Relevance
“…For example, Polito et al (2007) demonstrated similar blood pressure responses between heavy weights training with few repetitions compared with lighter weights training for more repetitions. Importantly, LL BFR resulted in elevated blood pressures when compared with LL and HL, findings similar to those previously reported for older hypertensive ( Pinto and Polito, 2016 ) and normotensive ( Vieira et al, 2013 ; Sardeli et al, 2017 ) individuals, as well as for healthy young men ( May et al, 2017 ). These findings have practical relevance for practitioners, especially if they are considering the implementation of BFR training in hypertensive patients.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Polito et al (2007) demonstrated similar blood pressure responses between heavy weights training with few repetitions compared with lighter weights training for more repetitions. Importantly, LL BFR resulted in elevated blood pressures when compared with LL and HL, findings similar to those previously reported for older hypertensive ( Pinto and Polito, 2016 ) and normotensive ( Vieira et al, 2013 ; Sardeli et al, 2017 ) individuals, as well as for healthy young men ( May et al, 2017 ). These findings have practical relevance for practitioners, especially if they are considering the implementation of BFR training in hypertensive patients.…”
Section: Discussionsupporting
confidence: 89%
“…There is evidence that a RT-BFR exercise session induces higher systolic and diastolic blood pressure increments and slower parasympathetic recovery compared with high intensity RT in elderly. 57 Nonetheless, a recent meta-analysis 58 showed that blood pressure responses to RT-BFR are similar to those observed during high intensity RT, regardless of the ageing group. Taken together, there is evidence suggesting that changes in blood pressure during RT-BFR are similar to traditional high intensity RT in different populations.…”
Section: Is Exercise With Blood Flow Restriction Safe?mentioning
confidence: 96%
“…However, young individuals have distinct haemodynamic responses to exercise compared with elderly. There is evidence that a RT‐BFR exercise session induces higher systolic and diastolic blood pressure increments and slower parasympathetic recovery compared with high intensity RT in elderly . Nonetheless, a recent meta‐analysis showed that blood pressure responses to RT‐BFR are similar to those observed during high intensity RT, regardless of the ageing group.…”
Section: Is Exercise With Blood Flow Restriction Safe?mentioning
confidence: 99%
“…Finger photoplethysmography According to methods described in our previous study 62 , systolic, diastolic and mean BP will be obtained using finger photoplethysmography, by Finometer Pro®(Finapres Medical System, Amsterdam, Holanda). The cuff is positioned at the distal phalanx of the middle finger of the right upper limb 63 .…”
Section: Blood Pressure W0/w4/ W8/ W12/ W16mentioning
confidence: 99%
“…[68][69][70] .Pulse wave velocity is obtained by SphygmoCor® (AtCor Medical) according to guidelines for clinical application of central and peripheral stiffness71 .Images of the left carotid common artery diameter 2cm under the carotid bifurcation will be collected by ultrasound (Nanomaxxtm, SonoSite, EUA), acquired with the linear transducer of 10-5MHz, at M mode, where a sequence of pictures for 5 seconds is registered62 . CC is calculated considering the difference between maximal and minimum diameters along the 5 seconds pulse, associated with systolic and diastolic BP at the same…”
mentioning
confidence: 99%